Agricultural experimental work - Gordon, James Scott (The University of Edinburgh, 1922)
Prior to 1890 no State aid was available in Great Britain for Agricultural education and experimental work and but little had been done in this direction by local authorities.

Research and experimental work, however, had not been altogether neglected as for many years the Royal Agricultural Society of England, the Highland and Agricultural Society of Scotland and the Rothameted Experimental Station had been engaged on investigations productive of much benefit to agriculture but, valuable as the results obtained by these bodies were, many problems of every -day interest to practical farmers had been left. unsolved.

When Parliament in 1890 for the first time made funds available for technical education under local authorities the Cheshire County Council was one of the first bodies to formulate for their County a. scheme of Agricultural education with a section for experimental work. For the five years from 1890 to 1895 the Council carried out experiments which had a direct bearing on the production of the common farm. crops and with the establishment by the Council in the latter year of an Agricultural and Horticultural College at Holmes Chapel this experimental work continued to develop rapidly, limited only by the extent of the College Farm.

It is necessary to emphasise the fact that all the experiments carried out in Cheshire were devised with the object of throwing light on problems which had a direct bearing on the agriculture of that County. This arose from the fact that questions were constantly being raised by the agricultural community to which the farming experience and practice handed down for generations provided no solution, and concerning which reliable information was not at that time available.

The scheme of experiments carried out in Cheshire comprised:- (1) Potato variety tests, the influence of manures on yield, etc. (2) The effect of wild white clover on . forming pasture. (3) The eradication of certain weeds prevalent in the County, e.g., Charlock. (4) Trials with varieties of turnips and mangolds. (5) Trials with varieties of wheat and oats.

It may here be mentioned that the Department of Agriculture and Technical instruction for Ireland. was established in 1900, when the results of the previous ten years' experimental work in Cheshire were known and their importance recognised. One of the earliest productions of the Department was a sche'ne of Agricultural experiments in the framing of which account was taken of the re sul t s of the Cheshire experiments in which it had been shown that the application of certain manurial mixtures had an appreciable effect in augmenting the yield of the several crops to which the mixtures were applied. 'The manurial experiments so drafted by the Department have been carries out in every County in Ireland during the past twenty years - the results confirming in a most striking manner those obtained in Cheshire prior to 1900.